2004
DOI: 10.1149/1.1723502
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Defects in Cu Metallization Structures by Electron-Beam Wafer Inspection

Abstract: A technique using an electron-beam to inspect wafers with Cu interconnects was developed. It can detect defects such as voids or incomplete contact failures with resistances of more than 10 7 ⍀ by utilizing the voltage contrast of a secondary electron image. The technique is performed by controlling the charging voltage of the interconnect while the electron-beam is irradiating the wafer. The charging voltage was found to depend on the conditions of the incident electron-beam, including the incident energy. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In particular, the authors have already reported that the grayscale of such SEM images depends on the variation in defect resistance due to an incomplete contact. [2][3][4][5] The prospective process flow applying our developed in-line resistance inspection using a noncontact type SEM inspection system is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors have already reported that the grayscale of such SEM images depends on the variation in defect resistance due to an incomplete contact. [2][3][4][5] The prospective process flow applying our developed in-line resistance inspection using a noncontact type SEM inspection system is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam (EB) inspection based on scanning electron microscopy (SEM) is useful to detect the hidden defects causing electrical failure such as contact failure, under-layer electric short, and leakages using voltage contrast [1][2][3][4]. It is difficult for those defects to be detected by optical wafer inspection tools.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SEM inspection using voltage contrast has the capability to detect electrical defects (such as incompletecontact defects) and shorts, for example. In particular, the authors have already reported that the grayscale of such SEM images depends on the variation of defect resistance due to an incomplete contact [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%